Synthesis of substrate-bound Au nanowires via an active surface growth mechanism - Wang, Xinglong (2018)
Advancing synthetic capabilities is important for the development of nanoscience and nanotechnology. The synthesis of nanowires has always been a challenge, as it requires asymmetric growth of symmetric crystals. Here, we report a distinctive synthesis of substrate-bound Au nanowires. This template-free synthesis employs thiolated ligands and substrate adsorption to achieve the continuous asymmetric deposition of Au in solution at ambient conditions. The thiolated ligand prevented the Au deposition on the exposed surface of the seeds, so the Au deposition only occurs at the interface between the Au seeds and the substrate. The side of the newly deposited Au nanowires is immediately covered with the thiolated ligand, while the bottom facing the substrate remains ligand-free and active for the next round of Au deposition. We further demonstrate that this Au nanowire growth can be induced on various substrates, and different thiolated ligands can be used to regulate the surface chemistry of the nanowires. The diameter of the nanowires can also be controlled with mixed ligands, in which another "bad" ligand could turn on the lateral growth. With the understanding of the mechanism, Au nanowire-based nanostructures can be designed and synthesized.